The Impact of Regional Expansion on Local Government (Study on Musi Rawas and North Musi Rawas Regency) - Adi Hayu Prasetiyo; M. Nur Budiyanto; Sena Putra Prabujaya (Universitas Muhammadiyah Ponorogo, 2026)
The purpose of this research is to understand and analyse the impact of regional expansion in the context of local government with a study of Musi Rawas Regency and North Musi Rawas Regency.Â The research method used is qualitative research. This research focuses on three parameters that become criteria and objectives in regional expansion, namely economic growth, regional financial performance, and community welfare which are tested using the impact evaluation method, namely comparative before - after from Finsterbusch & Motz (1980) in the dimension of â€˜difference between actual and expected impactâ€™ from Langbein (1980). Data collection techniques used interviews, observation, and documentation. The technique of determining informants is purposive sampling and snowball sampling analysis. The data analysis technique uses data analysis developed by Robert K. Yin (2016), namely compile database, disassemble data, reassemble data, interpret data, & conclude. The results showed that regional expansion in the parent region and DOB had an actual impact that was positive as expected through the parameters of economic growth, regional financial performance, and community welfare, but there were also unexpected and negative impacts. The positive impacts received by the community and local governments have not been proportional to the burden on the state budget for the expansion process and the transfer of funds each year to local governments. The results of this study indicate the need for strategies from the Mura and Muratara governments to improve and oversee community empowerment and regional superior commodities, infrastructure, and PAD, as well as equal distribution of teachers and health workers.